Compliance with a WHO guideline for cardiovascular disease prevention. A population based cross-sectional study in Argentina - Pablo Gulayin; Laura Gutierrez; Fernando Lanas; Nora Mores; Jacqueline Ponzo; Matías Calandrelli; Rosana Poggio; Vilma Irazola (Revista de la Facultad de Ciencias Médicas de Córdoba, 2024)
Introduction: Current recommendations for cardiovascular disease (CVD) prevention are guided CVD risk classification. This study aims to analyze the level of compliance with pharmacological and non-pharmacological recommendations outlined in the World Health Organization (WHO) CVD prevention clinical practice guideline within the general population of two cities in Argentina.